1969
DOI: 10.1037/h0028138
|View full text |Cite
|
Sign up to set email alerts
|

Paragraph organization of written materials: The influence of conceptual clustering upon the level and organization of recall.

Abstract: Forty-eight sentences, which associated eight attributes with six chessmen, were clustered in paragraphs by chessman, by attribute, or by rote group (randomized). One-half of 42 high school graduates were told the conceptual structure of the passage before reading. Subjects read the passages for three 5-minute periods-in orde'r to learn the information and to evaluate chess play. Free recall was required after each reading. With the organized passages, recall was about 50 per cent higher 'than with the rote gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
43
1
2

Year Published

1971
1971
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 17 publications
9
43
1
2
Order By: Relevance
“…One of the earliest demonstrations of this fact was provided by Deese and Kaufman (1957), who showed that as word lists became closer approximations to English prose, the normal serial position curve for word-list recall lost its recency portion, whereas the primacy portion of the curve became more exaggerated. Similar primacy effects for organized prose have appeared in more modern work (e.g., de Villiers, 1974;Frase, 1969;Meyer & McConkie, 1973), usually in the context of the "levels effect." This effect, which has been reported frequently (e.g., Johnson, 1970;Kintsch, Kozminsky, Streby, McKoon, & Keenan, 1975;Thorndyke, 1977), is that information that is at a high level of importance in the propositional structure of the passage content is recalled better than that at low levels.…”
Section: University Ofarizona Tucson Arizona 85721mentioning
confidence: 59%
“…One of the earliest demonstrations of this fact was provided by Deese and Kaufman (1957), who showed that as word lists became closer approximations to English prose, the normal serial position curve for word-list recall lost its recency portion, whereas the primacy portion of the curve became more exaggerated. Similar primacy effects for organized prose have appeared in more modern work (e.g., de Villiers, 1974;Frase, 1969;Meyer & McConkie, 1973), usually in the context of the "levels effect." This effect, which has been reported frequently (e.g., Johnson, 1970;Kintsch, Kozminsky, Streby, McKoon, & Keenan, 1975;Thorndyke, 1977), is that information that is at a high level of importance in the propositional structure of the passage content is recalled better than that at low levels.…”
Section: University Ofarizona Tucson Arizona 85721mentioning
confidence: 59%
“…In a typical study (Frase, 1969), subjects using a name concept strategy were superior to those using an attribute strategy, and both were superior to the scrambled order group. Sasson (1971) interrelated two different topics, a variant of the scrambled order method, and found in both instances that a thematic organization produced superior student achievement as compared to temporal (i.e., sentences included a date) and logical arrangements.…”
Section: Modification Of Current Feedback Strategies: a Text Synthesimentioning
confidence: 93%
“…Presenting the title after exposure to the text does not facilitate recall (Bransford & Johnson, 1972;Dooling & Mullet, 1973;Frase, 1969), suggesting that the locus of the effect is in acquisition. But the material that was used in these experiments was difficult and almost incomprehensible without a proper title, leaving open the possibility that titles may also play a role as a retrieval scheme, as suggested by Gagne (1969) and Gagne and Wiegand (1970).…”
mentioning
confidence: 99%